Bioethics as the ‘Third Culture’: Integrating Science and Humanities, Preventing ‘Normative Violence’ - Boutlas, George (Conatus - Journal of Philosophy, 2019)
Integrative Bioethics engages in descriptive and normative fields, or in two cultures, as Snow puts it in The Two Cultures and the Scientific Revolution, announcing though, in his later writings the emergence of a third culture that can mediate between the two. Thomas Kuhn in The Structure of Scientific Revolutions exposes the practice of a new paradigm of the teaching of history describing in fact the relation of science and humanities in the positivist era. The long standing reasons-causes debate that lay the groundwork of the implied incompatibility of the two cultures, as it reflects on the Collingwoodian anti-causalism of the philosophy of history, against Davidsonian causalism, may elucidate the problem of the ‘marriage’ of cultures. Taking a look on Collingwood’s absolute presuppositions and Carnap’s external to linguistic frameworks questions, will help us investigate the possibility of a coherent framework for integrated Bioethics. Can we frame a transdisciplinary field, where science and humanities as collaborating social practices, or as a new ‘cultural policy’ (according to Richard Rorty), will abstain from normative violence against each other?